Discontinuities: What is the value of having the lowest price or highest consumer rating on a price comparison website? - Charlie Lindgren (Institute of Retail Economics (HFI), 2021)
This paper examines price elasticities on a price comparison website and if there is a discontinuity in demand for retailers having the lowest price, or products having the highest consumer rating. Previous research is extended upon, with a larger, more recent, and more varied dataset, with retailers and products followed over a longer period. It is found that there is a statistically significant positive discontinuity in demand for retailers offering the lowest price. However, the results also show that the magnitude of the effect can vary substantially between product categories. The increase in demand ranges from 58% to 154%, with an average effect of 92%. The results pertaining to consumer ratings are found to be inconclusive. The importance for retailers of maintaining the lowest price therefore remains strong, while consumer ratings seem to have less of an impact on consumer demand.
Keywords: D22; D83; L11; L86; 330; Online retailing; e-commerce; price comparison websites; product ratings; lowest price